Construction and comprehensive analysis of a curoptosis-related lncRNA signature for predicting prognosis and immune response in cervical cancer - Liu, Li; Zheng, Jianfeng; Xia, Hongmei; Wu, Qiaoling; Cai, Xintong; Ji, Liyan; Sun, Yang (Frontiers in Genetics, 2023)
Cuproptosis (copper-ion dependent cell death) is an unprogrammed cell death, and intracellular copper accumulation, causing copper homeostasis imbalance, and then lead to increased intracellular toxicity, can affect the rate of cancer cell growth and proliferation. The aim of this study was to create a newly cuproptosis-related lncRNA signature that can be used to predict survival and immunotherapy in patients with cervical cancer, but also to predict prognosis in patients treated with radiotherapy and may play a role in predicting radiosensitivity. First of all,we found lncRNAs associated with cuproptosis between cervical cancer tumor tissues and normal tissues. By LASSO-Cox analysis, overlapping lncRNAs were then used to construct lncRNA signatures associated with cuproptosis, which can be used to predict the prognosis of patients, especially the prognosis of radiotherapy patients, ROC curves and PCA analysis based on cuprotosis-related lncRNA signatures and clinical signatures were developed and demonstrated to have good predictive potential. In addition, differences in immune cell subset infiltration and differences in immune checkpoint expression between high-risk and low-risk score groups were analyzed, and we investigated the relationship between this signature and tumor mutation burden.In summary, we constructed a lncRNA prediction signature associated with cuproptosis. This has important clinical implications, including improving the predictive value of cervical cancer patients and guiding individualized treatment.